Progesterone profile and ultrasonographic scanning of uterus during post partum period in Jakhrana goats - GOEL, A K; KHARCHE, S D; JINDAL, S K; KUMAR, S; RANJAN, R; SINGH, S P; BHUSHAN, S (The Indian Journal of Animal Sciences, 2016)
It is evident from our findings that oestrous cyclicity was not resumed during 60 days pp in Jakhrana female goats, as progesterone level remained at basal level (£ 1.00 ng/ml) during this period. The ELISA results were further supported by ultrasonographic examination which revealed that post partum uterus regained pre-gravid stage by day 45 pp. Transrectal ultrasonography was confirmed as a reliable tool to determine uterine involution in goats. Thus, the results suggest the possibility of sustaining next pregnancy in Jakhrana goats after 60 days pp. Moreover, based upon these findings, it is clear that interventions are possible by advocating hormonal therapy in order to induce and synchronize oestrus/ovulation at or after 60 days pp from the perspective of augmenting reproductive efficiency.